"I Tell My Partner Everything . . . (or Not)": Patients' Perceptions of Sharing Heart-Related Information With Their Partner. (May 2014) - Checton, Maria G.; Greene, Kathryn
This study is grounded in theories of information management. Patients with a diagnosed heart-related condition ( N = 253) completed a survey regarding their perceptions of sharing/not sharing information with a partner about their health condition. Data were analyzed using descriptive and inferential statistics. Results indicated that although most patients reported sharing "everything" with their partner, others reported not sharing certain topics such as health issues and physical symptoms/ailments. In addition, patients who reported sharing everything with a partner reported significantly greater communication efficacy, and breadth, depth, and frequency of communication about a heart-related condition compared with those who reported not sharing certain topics. Finally, as hypothesized, there were no significant group differences in terms of sharing specific physical and psychological health information. We discuss the findings and implications of the study for nursing practice.